Kesesuaian Lahan untuk Tanaman Kayu Putih sebagai Strategi Modifikasi Konservasi dan Kepentingan Nilai Tambah Ekonomi di Desa Cikembang, Kecamatan Kertasari, Kabupaten Bandung - Priswantoro, Andis Andis; Sulaksana, Nana Nana; Endyana, Cipta Cipta; Tri Mursito, Anggoro Anggoro (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2021)
ABSTRACT Cikembang Village, Kertasari District, Bandung Regency, is located in the Upper Citarum Sub-watershed. Cikembang, one of the water catchment villages, is a conservation area with eucalyptus plants. Eucalyptus plants in the category of Fast-Growing Species (FGS) can accelerate the process of succession of critical lands, restoration of peat ecosystems, are very adaptive to cultivate with agroforestry systems, support food security. However, the implementation of eucalyptus plants in Cikembang Village needs to be analyzed its impact on the conservation function and the importance of economic value-added. This study aims to form a conservation modification strategy and the importance of added value to the economy of eucalyptus cultivation by taking into account land suitability and its limiting factors. The soil fertility level approach is promising for eucalyptus growth in three land locations, namely: wet soil/Tb, slope/Tk, soil near springs/Tm, with attributes of elevation, slope, rainfall, temperature, acidity, and soil organic matter. With the storie methodâ€™s assessment, the soil is in the N1 category (currently unsuitable), and the root square is produced while the soil is in the S3 category (slightly marginal). The strategy for obtaining land use to accommodate cropping patterns for conservation and agricultural interests is by applying the silvicultural system techniques (integrating plant species, environmental modification, making terraces, setting spacing, and managing fertilization maintenance, including pest control). The study also tried to accommodate the approach to producing eucalyptus leaves as raw material for eucalyptus oil processing becomes an economic added value by refining eucalyptus oil. Keywords:Â eucalyptus, strategy, modification, conservation, added value Â ABSTRAK Kawasan Desa Cikembang, Kecamatan Kertasari, Kabupaten Bandung, terletak di Sub DAS Citarum Hulu. Cikembang salah satu desa tangkapan air menjadi daerah konservasi dengan tanaman kayu putih. Tanaman kayu putih kategori fast growing species (FGS) dapat mempercepat proses suksesi lahan kritis, restorasi ekosistem gambut, sangat adaptif dibudidayakan dengan sistem agroforestri, mendukung ketahanan pangan. Namun demikian, implementasi tanaman kayu putih di Desa Cikembang perlu dianalisis dampaknya terhadap fungsi konservasi dan kepentingan nilai tambah ekonomi. Penelitian ini bertujuan untuk membentuk strategi modifikasi konservasi dan kepentingan nilai tambah ekonomi budidaya tanaman kayu putih dengan memperhatikan kesesuaian lahan dan faktor pembatasnya. Pendekatan tingkat kesuburan tanah cukup menjanjikan untuk pertumbuhan kayu putih di tiga lokasi lahan yaitu: tanah basah/Tb, tanah kemiringan/Tk, tanah dekat mata air/Tm, dengan atribut elevasi, lereng, curah hujan, suhu, dan keasaman serta organik tanah. Dengan menggunakan pendekatan metode storie, diketahui bahwa tanah Desa Cikembang termasuk ke dalam kategori N1 (saat ini tidak sesuai), dan dengan menggunakan metode root square, dihasilkan bahwa tanah termasuk kategori S3 (sedikit marginal). Strategi yang digunakan untuk memperoleh tata guna lahan yang mengakomodasi pola tanam untuk konservasi dan kepentingan pertanian adalah pendekatan aplikasi teknik sistem silvikultur (pemaduan elemen spesies tanaman, modifikasi lingkungan, pembuatan teras, pengaturan jarak tanam, pengaturan pemupukan, pemeliharaan, termasuk pengendalian hama) serta pendekatan produksi daun tanaman kayu putih sebagai bahan baku olahan minyak kayu putih menjadi nilai tambah ekonomi dengan penyulingan minyak kayu putih. Kata kunci: kayu putih, strategi, modifikasi, konservasi, nilai tambah